1963
DOI: 10.2134/agronj1963.00021962005500020021x
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Corn Production as Affected by Moisture and Nitrogen Variables1

Abstract: Synopsis Moisture and nitrogen variables influenced sweet corn production at various growth stages‐seedling establishment, internode elongation, and pollination and grain development in a 3‐year investigation. Components contributing directly to yield were plant population, ears per plant, and weight per ear (including rows of kernels per ear, kernels per row, and weight per kernel). All were affected by irrigation and/or N fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Sweet corn yield was primarily affected by plant population per unit area, the number of usable ears per plant, row of kernels per ear, kernels per row and weight of individual kernels. Rows per ear, kernels per row and individual kernel weight may be combined into a single term, ‘weight per ear’ (Stanberry et al, 1963). Yield and other parameter relationships related to quantitative production are given in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweet corn yield was primarily affected by plant population per unit area, the number of usable ears per plant, row of kernels per ear, kernels per row and weight of individual kernels. Rows per ear, kernels per row and individual kernel weight may be combined into a single term, ‘weight per ear’ (Stanberry et al, 1963). Yield and other parameter relationships related to quantitative production are given in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Yield and quality have been greater when sweet corn was not subjected to water stress during silking and early ear development (Carolus and Schleusener, 1950). From a practical standpoint, it appears from the results obtained since 1958 that attention to irrigation scheduling is important only during the pollination period (Stanberry et al, 1963); during the establishment stage, transpiration usually is small, so that moisture stress is not important; during the internode elongation stage, a moderate soil moisture stress seems relatively unimportant; and after early ear development, the plant’s critical need for water appears to diminish. Thus, reducing soil water may be possible by allowing a slight irrigation deficit over the latter part of the season, although the difficulty of this approach is that this period coincides with the most critical growth stages (Gilley et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The pro duction of grain depended more than any other part upon the plentiful supply of moisture during the last 30-day period of growth. Stanberry et al (1963) observed that the continuous wet irrigation level with 0.2-atmosphere maximum soil moisture tension before irrigation was superior to the dry treatment in which irrigation occurred when soil moisture tension almost reached or equalled values causing overnight wilting. Vazquez (i960) in Puerto Rico, however, observed that irrigation did not influence com yields whenever there was 20 inches of welldistributed rainfall throughout the growing season.…”
Section: Effects Of Quantity and Distribution Of Irrigation Watermentioning
confidence: 95%
“…was considerably less than that obtained below that level. Stanberry et al (1963) concluded from an irrigated sweet corn experiment that most of the increase in yield was obtained with 75 lb. N/ac.…”
Section: Response In Short Term Experimentsmentioning
confidence: 99%
“…Stanberry et al (1963) observed an increase in com yield of about 9000 with supplemental N. They indicated that this in crease was due to the effect of N on the different yield com ponents, including kernel weight.…”
Section: Kernel Weightmentioning
confidence: 98%